Study Of Phosphodiesterase-5 Inhibitor (PDE5-I) And Anti-Diabetic In Diabetic Nephropathy In Animal Model - M. Uplenchwar, Pranay; Mohite, P. B. (Journal of Neonatal Surgery, 2025)
Diabetes mellitus affects around 600 million people worldwide, with neuropathy being one of its most common effects. The disease causes hyperglycemia, glycosuria, and ketoacemia, leading to pathogenic changes such as cell proliferation, vessel wall matrix rise, and capillary basement membrane alterations. Diabetes mellitus also has negative social, health, and financial consequences. The central problem being investigated is diabetic nephropathy, which progresses through stages, starting with hyperfiltration and microalbuminuria, leading to overt proteinuria and ultimately ESRD. Treatments like glycemic control and blood pressure management can potentially reverse kidney damage. The study assessed the effects of a combination of Tadalafil and Metformin on diabetic neuropathy caused by Streptozotocin in Albino wistar rats. The study evaluated blood glucose levels, serum creatinine, blood urea nitrogen, protein estimate in blood and urine, LDH, TNF, RAGE, IL-1, HMG B1, MDA, and TrxR. The results showed that the concentration of the drug in plasma increased in diabetic nephropathy, leading to increased bioavailability of the anti-diabetic drug in the presence of PDE5 inhibitors. The study's findings provide insight into the use of Metformin HCl (MET) and Tadalafil (TAL) in combination in clinical therapy, highlighting the potential benefits of using metformin, tadalafil, and their combination to treat diabetic nephropathy and kidney damage